Analisis Communication Skill Pada Pemasaran Tabungan Haji (Studi Kasus Bank Muamalat Kcp Stabat) - Khairi, Mhd Rizki; Aggraini, Tuti (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
Marketing communications is an important part of the overall marketing mission and determines marketing success. The purpose of marketing communication messages is to provide information regarding new policies, new services, new products. And the benefit is that sending informative messages can change people's knowledge and references to products and companies. This research uses qualitative research methods to obtain data which includes primary and secondary research data. Primary data was obtained from direct interviews. And secondary data was obtained from the Google Scholar database. The content analysis of this article is in accordance with the main topics discussed in the Google Scholar database. It is hoped that the results of this research will provide a deeper understanding of the effectiveness of persuasive communication and WoM to increase consumer awareness and trust in Tabungan Haji products. The implications of this research can help Islamic banking companies and related financial institutions develop more effective marketing campaigns, and strengthen the impact of WoM in building better relationships with potential customers. Furthermore, the findings of this research can contribute to the theoretical understanding of the dynamics of persuasive communication and WoM. In order to market products that have religious value.